Fauna de Gammaridea (Crustacea-Amphipoda) associada a ulva em trechos de litoral escarpado de Niterói e Angra dos Reis - RJ - Carvalho, Marylena (1977)
Collections of gammaridean Amphipoda were made at rocky interdital sites from coastal regions of Municipios de Niterói and Angra dos Reis (Rio de Janeiro, Brazil). The samples were collected only in ulva Which were dug up from the upper mediolitoral of points of collections of Baia Guanabara (Niterói), Atlantic litoral (Niterói) and Baia de Ilha Grande (Angra dos Reis).The fauna studied, about 1500 specimens, underwent fixing techniques, dissection and mounting on glass slides , about 500 samples; and were afterwards drawn in lucid camera making 26 plates with 295 illustrations. Taxonomic research the of gammarideans resulted in the elaboration of 3 keys for classification of the 8 species correspomding at the genus Elasmopus, Jassa and Hyale. From those 8 species studied, only Jassa falcata is known. Problems of taxonomy are discussed, with reference to the family of the genus Hyale and the affinities between some of its species. Maps, profiles, tide tables , chemical analyses, meteorological data form part of this paper.